Optimization of Traffic Police Public Education by Security and Safety Unit to Reduce Traffic Violations by Students in the Area of Resort Police Brebes - Viradhanti, Berliana Karla (Advances in Police Science Research Journal, 2024)
The high number of traffic violations in Brebes District indicates that there is still a lack of knowledge and public awareness in traffic. The perpetrators of traffic violations that occur in Brebes Regency are dominated by students. Actions that can be taken by the Security and Safety Unit of the Brebes Police Traffic Unit are through traffic police public education activities to increase public awareness in traffic so that the number of traffic violations can be reduced. The problem examined in this paper is why the traffic police public education by Security and Safety Unit to reduce traffic violations has not been carried out optimally. The purpose of this writing is to find efforts to optimize the traffic police public education by Security and Safety Unit in order to reduce traffic violations by students. This research was conducted in the jurisdiction of Brebes Police. The author uses a qualitative approach, field research method and data collection techniques with interviews, observations, and document reviews. The author uses the concept of optimization, the concept of public education by Security and Safety Unit, the concept of traffic violations, the concept of students, POAC theory, 6M management theory, and SWOT theory. The results showed that the traffic police public education by Security and Safety Unit carried out was not optimal due to the lack of quality and quantity of Security and Safety Unit’s human resources, limited budget owned, planning that was not in accordance with its implementation, uneven division of tasks, lack of media use in the implementation of dikmas lantas, and lack of evaluation from the leadership. Therefore, a problem solving is needed in optimizing the traffic police public education by Security and Safety Unit to reduce traffic violations by students.